Increased FGF23 serum level is associated with unstable carotid plaque in type 2 diabetic subjects with internal carotid stenosis. Issue 1 (December 2015) - Biscetti, Federico; Straface, Giuseppe; Porreca, Carlo; Bertoletti, Giovanni; Vincenzoni, Claudio; Snider, Francesco; Stigliano, Egidio; Arena, Vincenzo; Angelini, Flavia; Pecorini, Giovanni; Bianchi, Antonio; Landolfi, Raffaele; et al.
Abstract Background The object of this study was to investigate the potential role of FGF23 on plaque stability in type 2 diabetic patients with internal carotid artery stenosis. Methods In this retrospective observational study, we analyzed FGF23 serum level in 361 type 2 diabetic patients with internal carotid artery stenosis undergoing carotid endarterectomy and in 598 diabetic controls without carotid atherosclerosis. Results We found that FGF23 median serum levels was significantly higher in patients than in diabetic controls [67.7 (59.5–77.8) pg/mL and 43.89 (37.5–50.4), P < 0.001] and was significantly and independently associated with unstable plaque in patients with internal carotid artery stenosis [OR, 5, 71 (95 % CI, 2.09–15.29]. Conclusions We have found, for the first time, that FGF23 could be associated with unstable plaque in type 2 diabetic patients with internal carotid artery stenosis.